2021
DOI: 10.3390/cancers13205205
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1: A Pioneer of Nuclear Receptor Action in Breast Cancer

Abstract: The pioneering function of FOXA1 establishes estrogen-responsive transcriptomes in luminal breast cancer. Dysregulated FOXA1 chromatin occupancy through focal amplification, mutation, or cofactor recruitment modulates estrogen receptor (ER) transcriptional programs and drives endocrine-resistant disease. However, ER is not the sole nuclear receptor (NR) expressed in breast cancers, nor is it the only NR for which FOXA1 serves as a licensing factor. Receptors for androgens, glucocorticoids, and progesterone are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 172 publications
(322 reference statements)
1
21
0
Order By: Relevance
“…Interestingly, high affinity FOXA1 sites were remarkably less accessible compared to low affinity sites ( Extended Data Fig. 3a ), which is in agreement with the ability of this transcription factor to bind and subsequently open compacted chromatin, rendering it accessible to other transcription factors 25,26 . The fact that binding affinities of FOXA1 showed a strong correlation with H3K4me1 ( Extended Data Fig.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, high affinity FOXA1 sites were remarkably less accessible compared to low affinity sites ( Extended Data Fig. 3a ), which is in agreement with the ability of this transcription factor to bind and subsequently open compacted chromatin, rendering it accessible to other transcription factors 25,26 . The fact that binding affinities of FOXA1 showed a strong correlation with H3K4me1 ( Extended Data Fig.…”
Section: Resultssupporting
confidence: 72%
“…2b, Extended Data Fig. 3a ), possibly reflecting its ability to open condensed chromatin 26 . Here, FOXA1 was able to bind both promoters and enhancers with reduced accessibility, in particular at high affinity binding sites ( Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of POLR3G activated the expression of luminal fate-specific proteins FOXA1 and androgen receptor (AR). FOXA1 is not only required for developmental specification, but also for postnatal differentiation of breast epithelial cells into luminal cell types [ 45 , 46 ]. We also noticed that the expression of GATA3 was negatively correlated to the expression of POLR3G in clinical data ( Table S2 ).…”
Section: Discussionmentioning
confidence: 99%
“…FOXA1 , an androgen receptor (AR) chromatin-binding precursor in the prostate epithelium, was reprogrammed to neuroendocrine-specific regulatory elements [ 55 ]. In addition, a previous study revealed that FOXA1 , which established estrogen-responsive transcriptomes, was a pioneer of nuclear receptor action in breast cancer [ 56 ]. The interaction of FOXA1 with co-factors such as ESR1 and E2F1 enhanced the susceptibility of breast cancer [ 57 ].…”
Section: Discussionmentioning
confidence: 99%